2018
DOI: 10.1002/ana.25248
|View full text |Cite
|
Sign up to set email alerts
|

De novo gain‐of‐function variants in KCNT2 as a novel cause of developmental and epileptic encephalopathy

Abstract: Variants in several potassium channel genes have been found in developmental and epileptic encephalopathies (DEE). We report on 2 females with de novo variants in KCNT2 with West syndrome followed by Lennox-Gastaut syndrome or with DEE with migrating focal seizures. After in vitro analysis suggested quinidine-responsive gain-of-function effects, we treated 1 of the girls with quinidine add-on therapy and achieved marked clinical improvements. This suggests that the new spectrum of KCNT2-related disorders do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 23 publications
(29 reference statements)
5
64
1
2
Order By: Relevance
“…In K Na 1.2 but not K Na 1.1, the C-terminus also harbors a binding site for ATP, which function remains elusive (Bhattacharjee et al, 2003;Berg et al, 2007;Kaczmarek, 2013;Garg and Sanguinetti, 2014;Kaczmarek et al, 2016;Gururaj et al, 2017). In heterologous cells, functional analysis of mutant channels associated with EIMFS mostly revealed gain of function effects: potassium current was increased in cells expressing homomeric K Na 1.1 channels harboring either of the p. Val271Phe,p.Gly288Ser,p.Arg398Gln,p.Arg428Gln,p.Arg474His,p.Met516Val,p.Lys629Asn,p.Ile760Met,p.Pro924Leu or p.Ala934Thr missense mutations, and in cells expressing homomeric K Na 1.2 channels harboring either of the p.Arg190His or p.Arg190Pro missense mutations (Barcia et al, 2012;Rizzo et al, 2016;Villa and Combi, 2016;Ambrosino et al, 2018). A change in channel function has also been described in cells expressing the K Na 1.2 subunit harboring the p.Phe240Leu missense mutation: the mutant channel lost its selectivity to K + ions and gained permissiveness to Na + ions (Gururaj et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In K Na 1.2 but not K Na 1.1, the C-terminus also harbors a binding site for ATP, which function remains elusive (Bhattacharjee et al, 2003;Berg et al, 2007;Kaczmarek, 2013;Garg and Sanguinetti, 2014;Kaczmarek et al, 2016;Gururaj et al, 2017). In heterologous cells, functional analysis of mutant channels associated with EIMFS mostly revealed gain of function effects: potassium current was increased in cells expressing homomeric K Na 1.1 channels harboring either of the p. Val271Phe,p.Gly288Ser,p.Arg398Gln,p.Arg428Gln,p.Arg474His,p.Met516Val,p.Lys629Asn,p.Ile760Met,p.Pro924Leu or p.Ala934Thr missense mutations, and in cells expressing homomeric K Na 1.2 channels harboring either of the p.Arg190His or p.Arg190Pro missense mutations (Barcia et al, 2012;Rizzo et al, 2016;Villa and Combi, 2016;Ambrosino et al, 2018). A change in channel function has also been described in cells expressing the K Na 1.2 subunit harboring the p.Phe240Leu missense mutation: the mutant channel lost its selectivity to K + ions and gained permissiveness to Na + ions (Gururaj et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…EIMFS have a genetic origin and can be caused by de novo mutations in the KCNT1 gene encoding the K Na 1.1 subunit (Slack or Slo2.2) of K Na channels (Barcia et al, 2012;Ishii et al, 2013;McTague et al, 2013;Rizzo et al, 2016). More recently, two pathogenic mutations in the KCNT2 gene encoding the K Na 1.2 subunit (Slick or Slo2.1) have been reported (Gururaj et al, 2017;Ambrosino et al, 2018). K Na channels are voltagegated potassium channels that are activated by an increase of cytoplasmic Na + concentration.…”
Section: Introductionmentioning
confidence: 99%
“…However, in an order-randomized, blinded, placebo-controlled, crossover trial of quinidine in six ADNFLE patients, 33.3% (n = 2) of patients discontinued thera-py due to prolonged QT interval occurring at serum quinidine levels below the therapeutic range, and none of four patients who completed treatment trial showed 50% seizure reduction [49]. Other reports that included 25 EIMFS, two focal epilepsy, one West syndrome, and one NFLE patients, demonstrated that 31.0% (n = 9, including eight EIMFS) of patients experienced improvements in seizure activity due to quinidine administration while the others did not show any improvements [39,48,[50][51][52][53][54][55][56][57][58][59][60]. Lack of therapeutic response observed in the majority of patients is likely because exposure levels in the brain are too low to cause significant in vivo channel blockade [52].…”
Section: Kcnt1mentioning
confidence: 99%
“…Quinidine was not effective in ADNFLE patients [49]. Quinidine showed limited efficacy in EIMFS patients (responder rate=32%, n=25) [39,48,[50][51][52][53][54][55][56][57][58][59][60].…”
Section: Kcnt1 Eimfs Adnflementioning
confidence: 99%
“…These channels are abundantly expressed in the nervous system (Bhattacharjee et al, 2002;Bhattacharjee et al, 2005;Joiner et al, 1998;Liu et al, 2018;Rizzi et al, 2016), and play major roles in shaping neuronal electrical properties and regulating neurotransmitter release (Kaczmarek, 2013;Liu et al, 2014). Mutations of Slo2 channels cause epilepsies and severe intellectual disabilities in humans (Ambrosino et al, 2018;Cataldi et al, 2019;Evely et al, 2017;Gururaj et al, 2017;Hansen et al, 2017;Kawasaki et al, 2017;Lim et al, 2016;McTague et al, 2018;Rizzo et al, 2016), and reduced tolerance to hypoxic environment in worms (Yuan et al, 2003). Emerging evidence suggests that physiological functions of these channels depend on other proteins.…”
Section: Introductionmentioning
confidence: 99%